Nursing knowledge as relational ontology: Toward an enacted, technologically mediated, and globally situated understanding of nursing - Gil P. Soriano; Feni Betriana; Kathyrine Calong Calong; Joseph Andrew Pepito; Tetsuya Tanioka; Rozzano Locsin (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Despite substantial theoretical advancement, nursing knowledge continues to be framed by epistemological classifications rather than ontological clarification. The question of what nursing knowledge is, as a mode of existence, remains unanswered, despite existing frameworks that emphasize patterns, types, or domains of knowing. This paper argues that nursing knowledge is best understood as a relational ontology, a performative enactment emerging through practice rather than a collection of categorized components. Nursing knowledge is conceptualized as a unitary process manifested through embodied presence, interpretive meaning-making, and technologically mediated action. This paper illuminates how these aspects do not function as distinct domains but as a single, inseparable mode of being in clinical judgment and caring practices within digitally mediated contexts.